Footstrike evaluation in male runners: a comparison of lateral and medial video views against traditional motion capture - Mo, S.; Chu, A. S. Y.; Shao, S.; Chen, Y.; Hebert-Losier, K.; Li, L.; Cheung, R. T. H. (Journal of Biomechanics, 2025)
Footstrike evaluation is essential for understanding running biomechanics and is often performed in research and clinical settings using 2D video analysis. However, whether it is appropriate to analyse both right-left footstrike patterns from a single sagittal plane video is unclear. This study compared medial and lateral video views in assessing footstrike pattern and footstrike angle, using a motion capture system as the gold standard. We analyzed 4,800 footfalls from 20 healthy recreational runners during self-paced treadmill running, recruited through convenient sampling. Footstrike angle agreement was evaluated using Bland-Altman analysis, intraclass correlation coefficients (ICC), and root mean square error (RMSE). The mean difference in footstrike angle between the gold standard and lateral view was 0.40° (95% limits of agreement: 6.05° to -5.25°), while the medial view showed a mean difference of -1.31° (95% limits: 8.37° to -10.99°). ICC values indicated excellent agreement for both lateral (0.979) and medial (0.940) views to the gold standard. RMSE was lower for the lateral (2.91°) than medial (5.11°) view, suggesting greater precision. Footstrike pattern classification was assessed using Cohen`s kappa, revealing substantial agreement for the lateral view (k = 0.785, p < 0.001) and good agreement for the medial view (k = 0.606, p < 0.001). These results indicate that while both views demonstrate strong agreement, the lateral view aligns more closely with the gold standard in continuous and categorical assessments. Our findings suggest lateral video analysis may be preferable for footstrike evaluation in applied and clinical settings.